Experimentation of an Activated Carbon/Methanol Solar Refrigerator - Nyoman Sugiartha (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Adsorption refrigeration systems become promising alternative cooling technology for refrigeration and air conditioning applications. Thermal energy is a primary source of such systems for producing cooling capacity with less electricity usage compared to vapour compression systems. Solar energy with free-access and abundant availability in the tropics have great potential as a renewable heat source to drive the adsorption refrigeration systems through direct conversion from solar irradiation to the thermal energy. This paper describes experimental work on the performance of a solar adsorption refrigerator working with activated carbon/methanol pair in Bali area. The solar refrigerator has an adsorber with an effective surface area of 0.259 m2 enclosed in a double-glazed collector box. The cooling load of the evaporator is 1 kg of water sited inside a cooler box of 0.37 x 0.25 x 0.345 m size. The experimental tests were performed outdoor to determine system cooling capacity and solar COP. Test results indicated that the refrigerator capable of bringing down water temperature at 18 ⁰C, while the system cooling capacity and COP reach 47.5 kJ and 0.046. Moreover, it is supposed that the solar adsorption refrigerator can be applied to pre-cooling post-harvest agricultural products, mainly tomatoes, before distribution to the grocery stores or end consumers.